Methods study conducted on the Coca-Cola Bottler's Philippines, Incorporated Antipolo Plant, Production line no. 3 - Asio, Manuel P. Jr (College of Engineering, 1991)
The methods study conducted on Coca-Cola Bottlers' Philippines Incorporated Antipolo Plant seeks to improve the present Production Line No. 3 which produces the 8 ounces Coca-Cola softdrink. The study was conducted for three months. Starting last December it culminates by the submission of a formal report on the 19th of February 1991. The report includes the documentation of the present process and other related operations. The analysis and evaluation of the present and proposed methods and lastly recommending solutions to the problem. To understand the study better, the reader is advised by the group to read the background of the site. But in short terms the study was limited to the Production Line No. 3, the line which produces the 8 ounces Coca-Cola. The method study was to cover the point of pallet unloading the pallet loading. And most important is that the Coca-Cola is treated only as an input. To illustrate the method study done on the production line, the group prepared a flow diagram of the method study made with the important details included to facilitate information requirements that might be needed by the reader.